Willingness To Socio-Psychological Adaptation In Conditions Of Professional Activity Of Future Health Care Professionals - Ryzhenko, M. (Psychiatry, Neurology and Medical Psychology, 2016)
The article covers the basics of socio-psychological adaptation of future health care professionals. An aspect of the problem of socio-psychological adaptation is one of the most urgent at the current state, because the past and recent decades are characterized by the occurrence of various natural disasters, technological disasters and social cataclysms, which greatly undermine the adaptation process and lead to maladaptation. A necessary component of addressing these issues, formation and development of professional identityof future health care professional is adaptive behavior. In addition, the annual increase in social demand for training foreign experts in higher medical institutions of our country which is stipulated by its entry into the international educational system and promotion of Ukrainian educational services abroad, requires adapting to the professionally – oriented university environment and students from other countries. The study showed that the majority of medical graduates have a low level of adaptation. It means that future healthcare professionals should be encouraged to their future professional activities [1].